Deciphering Urban Morphology of Sadar Bazaar Areas of Colonial Cantonment Towns of Bengal Presidency in India - Eva Prasher; Sat Pal (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Colonial Cantonment towns in India are centers of cultural heritage that narrate the tale of British influences on the Indian city planning, art and architecture. The establishment of these towns was an introduction to a new form of settlement with unique requirements that included climatic, political and administrative needs. From the amalgamation of the indigenous and new techniques of city planning, emerged some specific features and elements. One such unique feature of these Colonial Cantonment towns is the Sadar Bazaar area which was the market cum residential space. These Sadar Bazaar areas are the containers of the rich tangible and intangible heritage and this study advocates the need of an efficient and case specific conservation, management and development plan for these spaces. With this aim, the paper emphasizes that the Sadar Bazaar areas should be understood as a unique typology with explicit features. To record the characteristic features and elements of these Sadar Bazaar areas, and to bring forth the issues and challenges these areas are facing in the present scenario, some cases were surveyed and studied. As Bengal Presidency held great importance in the Colonial history in India, the cases from this region were identified for the purpose of study.